THE INFLUENCE OF GENDER, FAMILY BACKGROUND, AND ENTREPRENEURSHIP EDUCATION ON STUDENTS’ ENTREPRENEURIAL INTEREST IN VOCATIONAL HIGH SCHOOLS - Widiantoro Baroto; Sora Baltasar (PT. Jurnal Center Indonesia Publisher, 2025)
This study investigates the influence of gender, family economic background, and entrepreneurship education on the entrepreneurial interest of vocational high school students in Depok. Using a quantitative explanatory design, data were collected from 123 students via structured questionnaires and analyzed through t-tests, F-tests, and multiple linear regression. The results show that all three variables positively affect entrepreneurial interest, with entrepreneurship education emerging as the strongest predictor (β = 0.641, p < 0.001), followed by family background (β = 0.239, p = 0.006) and gender (β = 0.228, p = 0.012). These findings indicate that students’ entrepreneurial intention is primarily shaped by formal entrepreneurship education, supported by family influence and gender-related differences in confidence and risk orientation. The study emphasizes the importance of practical entrepreneurship education and a supportive family environment in fostering entrepreneurial interest among vocational students, contributing to a sustainable youth entrepreneurship ecosystem.